Implementation of Voltage Control on a Multilevel DC-DC Boost Converter - Febi Ariefka Septian Putra; Sofyan Muhammad Ilman; Muhamad Amirul Muminin; Giga Verian Pratama; Dini Hariani Fitri Lubis; Annisa Izaty (Jurnal Teknik Elektro Indonesia, 2026)
A multilevel boost DC-DC converter is a solution for increasing DC voltage levels without requiring additional transformers, making it ideal for efficient power conversion applications and high-voltage systems. However, output voltage stability is often compromised due to load fluctuations and input voltage variations. To address this, this study aims to design and implement a control system based on the Proportional-Integral (PI) method to maintain the output voltage at a constant value of 200V from an initial input of 30V. The system was developed using an Arduino Nano microcontroller that acts as the main controller, regulating the PWM signal based on feedback from the voltage sensor. The converter circuit consists of a multilevel topology with one MOSFET, one inductor, and a cascaded array of capacitors and diodes. Tests were conducted under open-loop and closed-loop conditions, as well as with various resistive loads. The test results show that the PI method is able to provide good voltage stability and respond optimally to load changes, with minimal overshoot and fast steady-state time